Satu Dekade LAPOR: Tren Penggunaan Kanal Layanan SP4N - Muttaqin, Moh; Pusvita, Vita (Jurnal Pekommas, 2023)
The government built a National Public Service Complaint Management System (SP4N) to control public services. Complementing the implemented complaint service running through various channels at the national level, as well as Ministries, Institutions, and Local Governments (K/L/D), the government initiated the People's Online Aspirations and Complaints Service (LAPOR) featured digital channels. This research examines the SP4N service channel usage trends, especially in the 2013-2022 decade after LAPOR launched. Conducting descriptive analysis of the national SP4N usage data, the research reveals SP4N usage trends, channel usage trends, and channel contributions to SP4N usage. The SP4N usage in the last decade fluctuated but still has a positive growth trend. There has been a shift in the channel usage trend among digital channels, with the three most dominant channels being SMS, website and Android apps. The three digital channels also have the highest contribution, but traditional channels still emerge as one of the channels that need to be considered. Face-to-face is the only traditional channel included in the top 1000 usage and once reached an annual contribution of 1%. The research provides three recommendations: ineffective channel management policies, strengthening social media channels, and strategies for developing traditional channels.